Validity and Reproducibility of an Interviewer-administered Food Frequency Questionnaire for the Assessment of Riboflavin Intake in Malaysian Women in Selangor DUPLICATE - How, Ru En; Loh, Su Peng; Khor, Geok Lin (2019)
Introduction: The aim of this study was to assess the validity and reproducibility of a food frequency questionnaire (FFQ) specifically developed for the assessment of riboflavin intake among Malaysian women in Selangor. Methods: The study was carried out in Universiti Putra Malaysia (UPM), which consisted of 204 healthy women (102 Chinese and 102 Malay) aged between 19 and 45 years. The FFQs were interviewer-administered, which were completed twice; at the beginning of the study (FFQ-1) and two weeks thereafter (FFQ-2). A two-day 24-hour dietary recall (24DR) was interviewer-administered as the standard criteria method. Data were analyzed using Wilcoxon signed ranks test, Spearman correlation coefficient (SCC), intra-class correlation coefficient (ICC) and Bland-Altman plots to determine the validity and reproducibility. Results: Median riboflavin intake derived from 24DRs was significantly higher than FFQ-2 (p<0.01). Both FFQ-1 and FFQ-2 correlated significantly (p<0.01) with 24DRs with r-value of 0.264 and 0.227, respectively. As for reproducibility between FFQs, SCC value was statistically significant (p<0.01) at 0.545 whereby ICC value was 0.752, which considered as good. Most data points fell between the limits of agreements and were found closer to the horizontal line in the middle. However, the plots showed no linear trend existed between FFQ and 24DR over the range of mean riboflavin intake. Conclusion: The newly developed FFQ were found to be valid and relatively reproducible in the assessment of riboflavin intake among Malaysian women in Selangor.